Analyzing the dynamics of complicated and uncomplicated appendicitis during the COVID-19 pandemic in Seoul, Korea: a multifaceted time series approach - Kiook Baek; Chulyong Park (Epidemiology and Health)
OBJECTIVES This study investigated the impact of the coronavirus disease 2019 (COVID-19) pandemic and associated control strategies on the incidence of appendicitis in Seoul, using data from 2018 to 2020 from Korea’s National Health Insurance. METHODS We analyzed records of total, complicated, and uncomplicated appendicitis cases, as well as the ratio of complicated to uncomplicated appendicitis, using natural spline and piecewise regression models to identify trends and breakpoints. Bayesian structural time-series (BSTS) models were used to evaluate the causal impact of social distancing on appendicitis incidences. RESULTS The spline regression analysis indicated decreasing trends in both total and uncomplicated appendicitis cases. Conversely, the incidence of complicated appendicitis and the ratio of complicated to uncomplicated cases increased. Breakpoints for a decline in uncomplicated appendicitis and a rise in the ratio occurred at 31 weeks in 2020 (95% confidence interval [CI], 23.2 to 38.8) and at 33.9 weeks (95% CI, 28.3 to 39.6), respectively. The BSTS model demonstrated a 7.8% reduction in total appendicitis cases (95% credible interval [CrI], -12.1 to -3.3). It also showed a 17.4% decrease in uncomplicated cases (95% CrI, -22.2 to -12.3) and increases of 12.8% (95% CrI, 4.9 to 22.0) in complicated cases and 39.0% (95% CrI, 27.0 to 53.3) in the ratio of complicated to uncomplicated appendicitis. CONCLUSIONS The COVID-19 pandemic resulted in a decrease in both total and uncomplicated appendicitis cases, while the number of complicated cases increased. Reduced medical visits likely accounted for these changes. Strategies are needed to manage changes in disease pathophysiology resulting from altered healthcare utilization during health crises.